Assessing the Impact of Communication and Motivation on Employee Productivity: A Case Study of Turi Beach Resort, Batam - Aryo Dwi Prayogo; Hermansyah (Pt. Threeple Herphi Educate, 2025)
This study investigates the effect of communication and motivation on employee productivity within the hospitality industry, using Turi Beach Resort in Batam, Indonesia, as a case context. The research was driven by the operational challenges faced in resort environments, particularly those related to internal coordination and fluctuating work intensity. A quantitative approach with a causal-associative design was adopted, and data were collected through structured questionnaires from a sample of 147 employees. Multiple linear regression analysis was employed to examine the individual and combined effects of the variables. The results indicate that both communication (β = 0.307, p = 0.001) and motivation (β = 0.438, p = 0.000) significantly and positively influence employee productivity. Moreover, the model passed all classical assumption tests, confirming its statistical robustness. These findings highlight the strategic importance of internal communication in fostering clarity and coordination, and of intrinsic motivation in driving consistent employee performance. The study contributes to the human resource management literature by emphasizing the dual role of communication and motivation as complementary drivers of productivity in high-contact service industries. Managerial implications suggest the need for structured communication systems and motivation-enhancing policies to improve organizational outcomes.